Population Dynamic and Distribution of Bactrocera carambolae and Bactrocera dorsalis in Orchard Habitat in Different Geographical Areas - Kolopaking, Budiarto; Rizali, Akhmad; Affandi, Aminuddin; Hudiwaku, Syarron; Himawan, Toto (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2023)
Fruitflies, particularly Bactrocera carambolae and Bactrocera dorsalis, are significant pests that have the potential to diminish the quality and quantity of agricultural products. They may live in diverse habitats, particularly in agroecosystem habitats. Orchard habitats offer a source of food and development for fruit flies like B. carambolae and B. dorsalis not only in Java, notably Majalengka Regency, but also in Lombok Island and West Nusa Tenggara. Consequently, the purpose of there search is to observe (1) The population dynamic of B. carambolae and B. dorsalis in the orchard habitat. (2) Distribution of fruit flies B. carambolae and B. dorsalis trapping results in the orchard habitat. (3) Analyzing the factors affecting the presence of the fruit fly species B. carambolae and B. dorsalis in the orchard habitat. Fruitflies were sampled using the trap method between December 2021 and March 2022. In the orchard habitat on the mangosteen fruit commodity, the results indicated that B. carambolae and B. dorsalis had the largest population densities. Additionally, orchard locations on Lombok Island had the highest population density. Furthermore, fruitflies are more prevalent in perennial crops than in annual ones due to higher population density. Perennial crops are the ideal conditions for fruit fly development as compared to seasonal crops.